PEMANFAATAN MEDIA PEMBELAJARAN DALAM LAYANAN INFORMASI BIMBINGAN KONSELING - Azmatul Khairiah Sari (El-Rusyd, 2017)
Information service in counseling guidence is common thing for counseling guidence teacher. So that every teacher ought to mastered on managing class, understanding and others. Counseling guidence service as a prosess to learn for the students in order to make the goal. One of the way that teacher do is that by use media in learning.